Differential effects of age on neuromuscular transmission in partially denervated mouse muscle - Jacob, JM (J Neurosci, 1990)
The response of the neuromuscular junction to expansion of the motor unit after partial denervation (section of L5 root) was compared in soleus muscles from young (5–8 month) and old (25–30 month) mice. The object was to determine the relative capacity of young and old motor neurons to adapt to an enlarged functional field of innervation, and to delineate physiological parameters that are compromised under these conditions. Neuromuscular function was studied at 30, 60, and 120 d after partial denervation. The initial (18–23) and postoperative number (5–8) of motor units was the same in both age groups. Twitch strength declined in proportion to loss of motor units at 30 d but returned completely (young) or nearly completely (old) by 60 d. In old but not young muscle, the safety factor (assayed by twitch depression in low calcium) was decreased even before functional sprouting had occurred, indicating a reduced safety factor in nondenervated junctions. The proportion of fibers with “long” latencies (delay between stimulation and endplate potential) increased transiently (at 30 d) in young muscle but persisted without recovery at 120 d in regenerated junctions in old muscle. After partial denervation, decline in miniature endplate potential (mepp) amplitude, in mepp frequency, and in estimated quantal content of evoked release was relatively more pronounced in old than in young mice, and in the case of mepp amplitude and frequency, more persistent. Mepp amplitude was also decreased in presumed nondenervated junctions of old muscles.(ABSTRACT TRUNCATED AT 250 WORDS)